Effects of inter-firm technology transfer characteristics on degree of inter-firm technology transfer in international joint ventures - Raduan Che Rose; Sazali Abdul Wahab; Jegak Uli; Haslinda Abdullah (EuroJournals Publishing, 2009)
The main objective of this paper is to empirically examine the effects of four critical technology transfer characteristics: knowledge, technology recipient, technology supplier, and relationship characteristics on two distinct dimensions of degree of technology transfer, namely, degree of tacit and explicit knowledge. Using the quantitative analytical approach, the theoretical model and hypotheses in this study were tested based on empirical data gathered from 128 joint venture companies registered with the Registrar of Companies of Malaysia (ROC). Data obtained from the survey questionnaires were analyzed using the correlation coefficients and multiple linear regression analyses. The results revealed that relationship characteristics have the strongest significant effects on both degrees of tacit and explicit knowledge followed by technology supplier and recipient characteristics. Contrary to the study’s prediction, but still consistent with the recent development in literature, knowledge characteristics have only significantly affected degree of explicit knowledge not degree of tacit knowledge. The study has bridged the literature gaps by providing empirical evidence on the effects of four critical technology transfer characteristics: knowledge, technology recipient, technology supplier, and relationship characteristics on two distinct dimensions of degree of inter-firm technology transfer: degree of tacit and explicit knowledge in IJVs in a single model.